The effectiveness of a core muscles stability program in reducing the postural sway of adolescent archers: a panacea for a better archery performance - Suppiah Pathmanathan K., Kee Kiet Tomny Wong, Musa Rabiu Muazu, Abdullah Mohamad Razali, Lee Jeffrey Low Fook, Musawi Maliki Ahmad Bisyri Husin (IJPHY, 2017)
The effectiveness of a core muscles stability program in reducing the postural sway of adolescent archers: a panacea for a better archery performance by Suppiah Pathmanathan K., Kee Kiet Tomny Wong, Musa Rabiu Muazu, Abdullah Mohamad Razali, Lee Jeffrey Low Fook, Musawi Maliki Ahmad Bisyri Husin,